2010
DOI: 10.1111/j.1365-2524.2009.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

‘My biggest fear was that people would reject me once they knew my status…’: stigma as experienced by patients in an HIV/AIDS clinic in Johannesburg, South Africa

Abstract: Stigma is not a new concept; however, it remains highly significant in the context of HIV/AIDS in South Africa. There is wide consensus that HIV/AIDS-related stigma compromises the well-being of people living with the disease. This paper is part of a larger study that seeks to understand the social and cultural complexity related to the provision and outcomes of antiretroviral therapy (ART) in South Africa. It explores and analyses how patients on ART perceived and experienced stigma and how it has shaped thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
107
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 27 publications
7
107
1
1
Order By: Relevance
“…Repeated experiences of abuse and discouragement to participate in treatment programmes and attend care facilities could lead to diminished physical and mental health (Greeff et al, 2008). Isolation or decreased social participation of PLWH stems from living while fearing stigma and thus minimising their exposure to others (Gilbert & Walker, 2010) which in turn leads to poor participation in healthcare as well as in personal and employment relationships . A further outcome of HIV stigma for PLWH relates to self-isolating behaviour to prevent HIV-transmission to others and to minimise secondary (associated) stigma directed at those living close to them (Salter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated experiences of abuse and discouragement to participate in treatment programmes and attend care facilities could lead to diminished physical and mental health (Greeff et al, 2008). Isolation or decreased social participation of PLWH stems from living while fearing stigma and thus minimising their exposure to others (Gilbert & Walker, 2010) which in turn leads to poor participation in healthcare as well as in personal and employment relationships . A further outcome of HIV stigma for PLWH relates to self-isolating behaviour to prevent HIV-transmission to others and to minimise secondary (associated) stigma directed at those living close to them (Salter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration that disclosure of HIV status is inevitable in support groups; individuals may fear social rejection and discrimination [14]. Stigma remains a significant concern within the health care service field across societies and limits the potential value of HIV treatment care and support [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The results also showed that HIV-infected women were more impaired in terms of the QoL. This could be because HIVinfected women who are already socially excluded by social stigma (Gilbert & Walker, 2010) now have to cope with UI, which can be embarrassing. However, UI can be avoided or corrected, because effective treatments are available (Handa et al 2007;Mantle, Haslam & Barton 2004).…”
Section: Discussionmentioning
confidence: 88%
“…The authors stated that the decreased societal functioning might be due to cultural and social reactions to the virus (Larrabee et al 1996). Despite the stigma associated with HIV still being rife in South Africa (Gilbert & Walker, 2010), a decrease has been noted (Mall, Middelkoop, Mark, Wood, & Bekker, 2013). The improved social interaction could be due to an increase in knowledge about the virus, resulting from South Africans being more exposed to HIV due to the high prevalence rates (Mall et al 2013) and therefore socially aware of HIV.…”
Section: Discussionmentioning
confidence: 99%